KOMUNIKASI DAN INTERAKSI SOSIAL PADA LANSIA SELAMA MASA PANDEMI COVID-19 DI KABUPATEN PEMALANG - Dwiyanti Purbasari; Didik Rinanto (Jurnal Kesehatan Mahardika, 2022)
Aging has an impact on all aspects of spiritual biopsychosocial and quality of life. Susenas data (2020) shows that 9.80% of the elderly live alone. The Central Statistics Agency data (2020) shows that almost half of the elderly experience health complaints, both physical and psychological (48.14%)). The purpose of this study was to identify the relationship between communication skills and social interaction in the elderly during the COVID-19 pandemic in Pemalang Regency. This type of research uses descriptive correlation. The sample is 44 elderly people. The communication ability questionnaire instrument has r results 0.489 - 0.910 with r table = 0.423 and the social interaction questionnaire has r values ​0.447 - 0.857 with r table = 0.423. Data analysis using chi square with p-value 0.05. The research was conducted in June – July 2021 in the working area of ​​the Bantarbolang Public Health Center at Pemalang Regency. The results showed that 84.1% of respondents were able to communicate well, 79.5% of respondents has good social interaction, and there was a correlation between communication skills and social interaction in the elderly in Pemalang Regency (p value = 0.0001; α = 0.05). Communication skills are one of the supports in social interaction for the elderly. Public health center can develop health service programs and improve the quality of life of the elderly in integrated coaching posts.